On President Zviad Gamsakhurdia’s negative attitude towards the Commonwealth of Independent States (CIS) /Analysis of the Alma-Ata meeting/ Memory - Burchuladze, Nemo (Actual Problems of Kartvelology, 2019)
Rare in the history of mankind is an event of such significance as the collapse of the USSR, the full analysis of which, the reasons for which, and the study and assessment of the role of the states and individuals involved in it, is a difficult, long process and will require the work and research of many generations. The first President of Georgia, Zviad Gamsakhurdia, whose 80th anniversary we celebrate today, endured the greatest physical and spiritual pain to bring freedom to our country. His contribution is outstanding in saving the world from this metastatic malignant tumor, the empire of evil - the USSR. Of course, the civilized world has been trying to dismantle the Soviet Union, “Russian socialism”, which was worse than fascism, since its foundation, but it took 70 years. The economic and political crisis in the 1980s forced the rulers of the empire to give people (perhaps strange to today's generation) the right to express their own opinion, as they themselves called it - pluralism. However, they failed to take into account that both people and nations demanded the main thing - freedom. Non-Russian dissidents became especially active. Russian dissidents wanted to ennoble the empire - to democratize it, while the rest found the term - "democratic empire" unacceptable and incomprehensible, and they shifted the emphasis to national freedom, since personal freedom is unthinkable in an enslaved nation. National liberation organizations and political parties were formed and activated in the Soviet republics, among which Georgia and the leader of its liberation movement, Zviad Gamsakhurdia, held the leading position. The empire, in agony, resorted to a tried and tested method and on April 9, 1989, in Tbilisi, protesters who had taken to the streets demanding state independence, including those on hunger strike, were crushed with pickaxes, and hundreds of people died over the years from poison gas prohibited by international norms, but this not only frightened them, but also strengthened their ability to fight against the invaders. In the spring of 1990, the national movement, which actually led the processes, adopted a resolution of the Supreme Council of the Georgian SSR, according to which Georgia was occupied by Russia in 1921. On October 28 of the same year, the first multi-party elections in the history of the USSR were won by the bloc “Round Table - Free Georgia”, whose unconditional leader was Zviad Gamsakhurdia, who was elected Chairman of the Supreme Council of Georgia (I, my children and grandchildren are proud to have been his deputy). To this day, these elections are the only ones in Georgia in which not a single loser has ever had even a single vote rigged.